The Effect of Performance Measurement on Budget Execution with the Formulation of Performance Indicators on Budget Implementation of KPPN Blitar Service Scope - Laili, Nurina Risfaqul; Citra Mulya Sari (HM Publisher, 2022)
This study aims to analyze the effect of performance measurement with the formulation of performance indicators of budget implementation (IKPA) on the implementation of the budget. Performance measurement in this study is a systematic process to assess whether the planned program/activity is in accordance with the plan and, more importantly, whether it has achieved the success that was the target at the time of planning. Through a performance measurement, the success of a government agency will be more considered, and the ability of the agency will be based on the resources it manages. This is useful for achieving results in accordance with the planned plans so that strategic planning can advance the economy. Performance indicators of budget implementation are needed as a tool to monitor and evaluate as well as to measure the quality of financial implementation in order to encourage changes in state financial management behavior. In 2020, new regulations emerged with the addition of new indicator formulations, the variables used were value data from the old and new formulations of performance indicators for budget implementation. The analytical method used is a quantitative method, research instrument test, classical test, linear test, and partial and simultaneous test. The findings in this study indicate that: First, the formulation of the Old IKPA Assessment has a significant positive effect on Budget Implementation. Second, New IKPA Assessment has a significant positive effect on the budget implementation.